Learning-centred assessment validation framework: A theoretical exploration - Ijiwade, Oluwaseun; Alonzo, Dennis (Critical Studies in Teaching and Learning, 2023)
Classroom-based assessment validation has received considerable critical attention and many conceptualisations have emerged. While these conceptualisations are helpful in advancing our assessment knowledge, there is a need for a more learning-oriented teacher assessment practice validation. This paper builds on previous validation theories and approaches to redefine the validity of classroom-based assessment in terms of practical, useful, and trustworthy interpretation and uses of classroom assessment in enhancing learning and teaching. Further, the paper sets relevant inferences and prioritises teachers as sources of evidence in assessment evaluation based on pragmatic principles and Vygotsky’s sociocultural theory. This explication is valuable in exploring a learning-centred validation approach for evaluating classroom assessment. The paper suggests practical principles for evaluating learning-oriented, teacher-based assessment. Lastly, the paper concludes by articulating implication of the approach in any contemporary assessment system.